Label as you fold: methyltransferase-assisted functionalization of DNA nanostructures. Issue 39 (1st October 2020) - Heck, Christian; Torchinsky, Dmitry; Nifker, Gil; Gularek, Felix; Michaeli, Yael; Weinhold, Elmar; Ebenstein, Yuval
Abstract : The DNA methyltransferase M.TaqI is presented as a new tool to label DNA nanostructures covalently with fluorophores and azide groups. Abstract : Non-DNA labels are key components for the construction of functional DNA nanostructures. Here, we present a method to graft covalent labels onto DNA origami nanostructures in an enzymatic one-pot reaction. The DNA methyltransferase M.TaqI labels the DNA nanostructures with azide groups, which serve as universal attachment points via click chemistry. Direct labeling with fluorescent dyes is also demonstrated. The procedure yields structures with high fluorescence intensities and narrow intensity distributions. In combination with UV crosslinking it enables the creation of temperature-stable, intense fluorescent beacons.